Driven or lacking access: Integration types as a subdimension of the affect consciousness construct - Vølstad, Astrid Gravdal; Salas, Maria Ingunnsdatter; Solbakken, Ole André (Frontiers in Psychology, 2023)
This article examines integration types as a sub-dimension of the affect consciousness construct to account for individual differences in how problems with affect integration are manifested. The two integration types driven and lack of access describe prototypical ways of experiencing and expressing affect, differentiating between problems characterized by too much or too little affect. Archival data from a non-clinical sample (n = 157) was used to examine the validity and reliability of integration type scales derived from the Affect Integration Inventory (AII 2.0). Internal structure was assessed through confirmatory factor analyses (CFAs) performed by structural equation modelling. External criterion validity was examined through tests of patterns of hypothesized associations between integration types and specific types of interpersonal problems (measured by the Inventory of Interpersonal Problems; IIP-64). CFAs indicated acceptable fit for the different integration type scales and overall construct structure. Distinct sinusoidal patterns of correlations between integration types and interpersonal problems were found for the various affects examined. All correlation patterns had good fit (GoF ≥ .91), with significant differences in magnitude between peak and low point correlations.